The Ethics of Memory and Memoir Writing. Charles Péguy and Romain Gary - Aronowicz, Annette (Perichoresis, 2024)
In this paper, I will draw on two twentieth-century French writers and extract from their works their ideas about memory and memoir writing. The first, the poet and philosopher Charles Péguy wrote a great deal about memory, bringing the philosophy of Henri Bergson into realms of daily life that the philosopher himself did not. Not all of Péguy’s meditations on memory are related to memoir writings, and yet they provide a possible frame for anyone who would want to engage in such a task. I will focus on some of his points about time and aging, give some examples from his projected confessions, and relate them to the writing of memoirs as he saw it. The second author, Romain Gary was a prolific novelist, whose works were among the greatest best sellers in post-War France. I will focus on his literary memoir, Promise at Dawn. Gary does not write directly about memoir writing. His ideas on it are embedded in his autobiographical narration, however, and it is these ideas that I shall extract and illustrate. Much separates these two authors’ views on memory and memoirs. Despite their differences, I would like to argue that both authors focus on the ethics of memory and memory writing. That ethics revolves not so much on telling the literal truth, the getting this or that detail correctly, but in capturing and conveying the commitments that have marked one’s life, and capturing them in such a way that they do not coincide with the current pieties about the past. Memoir writing for both authors is a way of responding to the times, a kind of critique of contemporary society.